Health economic evaluations for Indonesia: a systematic review assessing evidence quality and adherence to the Indonesian Health Technology Assessment (HTA) GuidelineResearch in context - Kinanti Khansa Chavarina; Dian Faradiba; Ella Nanda Sari; Yi Wang; Yot Teerawattananon (Elsevier, 2023)
Summary: Background: The Government of Indonesia implemented health technology assessment (HTA) to ensure quality and cost control in the National Health Insurance Program (Jaminan Kesehatan Nasional/JKN). The current aim of the study was to improve the usefulness of future economic evaluation for resource allocation by appraising current methodology, reporting, and source of evidence quality of studies. Methods: The inclusion and exclusion criteria were applied to search for relevant studies using a systematic review. The methodology and reporting adherence were appraised according to Indonesia's HTA Guideline issued in 2017. The differences in adherence before and after the guideline dissemination were compared using Chi-square and Fisher's exact tests for methodology adherence wherever appropriate, and the Mann-Whitney test for reporting adherence. The source of evidence quality was assessed using evidence hierarchy. Two scenarios of the study start date and the guideline dissemination period were tested using sensitivity analyses. Findings: Eighty-four studies were obtained from PubMed, Embase, Ovid, and two local journals. Only two articles cited the guideline. No statistically significant difference (P > 0.05) was found between the pre-dissemination and post-dissemination period with respect to methodology adherence, except for outcome choice. Studies during the post-dissemination period showed a higher score for reporting which was statistically significant (P = 0.01). However, the sensitivity analyses revealed no statistically significant difference (P > 0.05) in methodology (except for modelling type, P = 0.03) and reporting adherence between the two periods. Interpretation: The guideline did not impact the methodology and reporting standard used in the included studies. Recommendations were provided to improve the usefulness of economic evaluations for Indonesia. Funding: The Access and Delivery Partnership (ADP) hosted by the United Nations Development Programme (UNDP) and the Health Systems Research Institute (HSRI).